Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Open Ended Problem Pada Materi Pokok Lingkaran - Telaumbanua, Yakin Niat; Waruwu, Yutiani (Indonesian Research Journal on Education, 2022)
This study was conducted to determine the level of validity of the Student Activity Sheet based on Open ended problems in the circle material in mathematics learning, the level of practicality of the Student Activity Sheet based on Open ended problems on the circular material in mathematics learning and the level of effectiveness of the Student Activity Sheet based on the Open ended problem in mathematics learning. circle material in mathematics learning. This research method uses Research and Development (R&D) which begins with a preliminary study followed by the product development and assessment stage. The development model used is a 4-D model consisting of four stages, namely definition, design, development, and dissemination. This research was conducted at SMP Negeri 1Sirombu. The results of the research analyzed were: (1) The results of the validation carried out by material experts, linguists, and design experts stated that the teaching materials were LKPD based on open ended problems on the main material of the class VIII circle. validation is 4.5 with a valid category. The results of validation by linguists, obtained a validation value of 5 with a very valid category. The results of validation by design experts,obtained a validation value of 4.4 with a valid category. (2) The level of practicality in individual tests with a percentage of 90.3% is very practical, 89% small group trials are very practical and 88% field trials are very practical. (3) The level of effectiveness with a percentage of 89% is very effective. (4) The results of product distribution data that have been developed based on the activeness of students are 91% and are categorized as very active. Based on the data above, the Student Activity Sheet based on open ended problems on the subject matter of circles can be used as an alternative to mathematics teaching materials in class Junior High School at VIII class.